Prevalence and risk factors for dangerous abbreviations in Malaysian electronic clinical notes - Mohd Sulaiman, Ismat (SAGE Publications, 2023)
Medical abbreviations can be misinterpreted and endanger patients' lives. This research is the first to investigate the prevalence of abbreviations in Malaysian electronic discharge summaries, where English is widely used, and elicit the risk factors associated with dangerous abbreviations. We randomly sampled and manually annotated 1102 electronic discharge summaries for abbreviations and their senses. Three medical doctors assigned a danger level to ambiguous abbreviations based on their potential to cause patient harm if misinterpreted. The predictors for dangerous abbreviations were determined using binary logistic regression. Abbreviations accounted for 19% (33,824) of total words; 22.6% (7640) of those abbreviations were ambiguous; and 52.3% (115) of the ambiguous abbreviations were labelled dangerous. Increased risk of danger occurs when abbreviations have more than two senses (OR = 2.991; 95% CI 1.586, 5.641), they are medication-related (OR = 6.240; 95% CI 2.674, 14.558), they are disorders (OR = 7.771; 95% CI 2.054, 29.409) and procedures (OR = 3.492; 95% CI 1.376, 8.860). Reduced risk of danger occurs when abbreviations are confined to a single discipline (OR = 0.519; 95% CI 0.278, 0.967). Managing abbreviations through awareness and implementing automated abbreviation detection and expansion would improve the quality of clinical documentation, patient safety, and the information extracted for secondary purposes.